2006
DOI: 10.1080/08985620600565409
|View full text |Cite
|
Sign up to set email alerts
|

Why are some Spanish manufacturing firms internationalizing rapidly? The role of business and institutional international networks

Abstract: The aim of this paper is to examine the profile of international manufacturing firms located in Spain. After reviewing previous research on the internationalization of small and medium companies, we will look at whether the relevance of certain characteristics and key internationalization factors differ between firms following the traditional gradual internationalization process and firms internationalizing rapidly. Basically, economic literature points out that clients', suppliers', competitors' and instituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
2
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 87 publications
5
59
2
3
Order By: Relevance
“…Unlike previous studies, which evaluated the impact of belonging to clusters on internationalization in export performance (BECCHETTI; ROSSI, 2000; MITTELSTAEDT; WARD; NOWLIN, 2006;BELSO-MARTINEZ, 2006;BECCHETTI;PANIZZA;OROPALLO, 2007). These findings indicate that, depending on the cluster in which the winery is located, this impact will be different.…”
Section: H2contrasting
confidence: 52%
See 1 more Smart Citation
“…Unlike previous studies, which evaluated the impact of belonging to clusters on internationalization in export performance (BECCHETTI; ROSSI, 2000; MITTELSTAEDT; WARD; NOWLIN, 2006;BELSO-MARTINEZ, 2006;BECCHETTI;PANIZZA;OROPALLO, 2007). These findings indicate that, depending on the cluster in which the winery is located, this impact will be different.…”
Section: H2contrasting
confidence: 52%
“…Confirming the argument of Zhao and Zou (2002) In addition, the results of these studies are contradictory: on the one hand, the results indicate the existence of a positive influence of the geographical agglomeration of companies in export performance (BECCHETTI;ROSSI, 2000;MITTELSTAEDT;WARD;NOWLIN, 2006;BELSO-MARTINEZ, 2006;BECCHETTI;PANIZZA;OROPALLO, 2007); on the other, studies that found no relationship or even a negative influence of geographic concentration on the export performance (ZHAO; ZOU, 2002;MACCARINI;SCABINI;ZUCCHELLA, 2003). Intermediately, Fernhaber, Gilbert andMcDougall (2008) found that the concentration of companies in a cluster relates positively with the intensity of exports of new projects to some extent, from which the relationship becomes negative.…”
Section: T H E I N T E R N At I O N a L I Z At I O N Of Companies Belmentioning
confidence: 43%
“…Research in this theme identifies and explores such patterns, sometimes identifying influences and outcomes. For example, factors enabling rapid internationalization include client followership, the firm's knowledge intensity and its social capital (Bell, 1995;Belso-Martinez, 2006;Litvak, 1990;McNaughton, 2001;Yli-Renko et al, 2002), and its perception and management of risk (Acedo and Jones, 2007;Shrader et al, 2000). Early internationalization can enhance firm growth , while entering diverse international markets can increase technological learning and improve performance .…”
Section: Internationalization (Emerged 1990)mentioning
confidence: 97%
“…To the extent Colombian small and medium-sized firms indeed have few, short term, and unimportant relationships with their customers and suppliers, (Fairbanks 2000) they gain little knowledge about foreign markets, and thus cannot count on utilizing these relationships to gain such knowledge (Gomes-casseres 1997, Johanson/Mattsson 1988, Pla-Barber 2001. this may explain differences with other research which found sMes in the more developed context of spain following customers due to their significant links, but remaining unaffected by internationalized competitors (Belso-Martinez 2006).…”
Section: Discussionmentioning
confidence: 83%